Primary intestinal diffuse large B-cell lymphoma: novel insights and clinical perception - Chen, Xiaojun; Wang, Jing; Liu, Yanquan; Lin, Suxia; Shen, Jianzhen; Yin, Yue; Wang, Yili (Frontiers in Oncology, 2024)
Background: Extranodal Non-Hodgkin lymphoma (NHL) is more prevalent in the gastrointestinal (GI) tract than in other sites. This study aimed to explore the clinical features and prognostic factors of primary intestinal diffuse large B-cell lymphoma (PI-DLBCL), in order to provide new references for basic research and clinical diagnosis and treatment of the rare extranodal malignant lymphoma.The clinical data of 88 patients with PI-DLBCL admitted to Fujian Medical University Union Hospital from June 2011 to June 2022 were retrospectively studied, the clinical and pathological features, diagnosis and treatment process and prognosis of PI-DLBCL were analyzed, and univariate and multivariate analysis of prognostic factors was carried out. The Kaplan-Meier method was used for survival analysis. Meanwhile, the latest literature from PubMed was retrieved to systematically discuss the research progress in the diagnosis and treatment of PI-DLBCL.Results: Among the 88 patients with PI-DLBCL included in this study, 60 cases were males (68.18%), 28 cases were females (31.82%), and 62 patients (70.45%) were complaining of abdominal pain, and the second most common clinical manifestation was changes in bowel habits in 16 (18.18%), with a median age of onset of 57 (17-82) years. The first-line treatment regimen was surgery combined with R-CHOP chemotherapy (56.82%). The median follow-up time was 72 (1-148) months, 51 (57.95%) of 88 patients with PI-DLBCL survived, 30 patients (34.09%) died, 7 patients (7.95%) were lost to follow-up, and the PFS rates of 1-year, 3-year and 5-year were 57.95%, 29.55% and 15.91%, and the OS rates of 1-year, 3-year and 5-year were 79.55%, 45.45% and 28.41%, respectively. The results of multivariate Cox analysis showed that Lugano stage may be an independent prognostic factor affecting OS and PFS in PI-DLBCL patients.PI-DLBCL is more common in middle-aged and elderly men, clinical manifestations lack specificity, first-line treatment is mainly surgery combined with standard chemotherapy regimens. The Lugano stage may be an independent prognostic factor affecting OS and PFS in PI-DLBCL patients.